Solution-based fullerene-free route enables high-performance green-selective organic photodetectors - Yang Cao; Jianjun Mei; Kai Xia; Ting Zhao; Jing Zhao; Nicola Gasparini; Vincenzo Pecunia (JPhys Materials, 2022)
Ongoing developments in machine vision, wearables, and the Internet of Things have led to strong demand for easy-to-fabricate, color-selective photodetectors. Narrowband-absorption-type (NBA) printable organic photodetectors provide an attractive solution, given their spectral robustness and fabrication simplicity. However, a key remaining challenge to realizing their potential is to concurrently achieve high photoconversion efficiency and spectral selectivity. Herein, this challenge is tackled by investigating a non-fullerene-based route to green-selective, solution-based photodetectors. Soluble phthalocyanine acceptor PhO-Cl _6 BsubPc is considered due to its high absorption selectivity to green photons. Blends with soluble quinacridones are pursued to realize the ideal of a donor:acceptor layer selectively absorbing the target photons throughout its volume. A latent-pigment route to the solution-based deposition of linear trans -quinacridone (QA) enables well-intermixed QA:PhO-Cl _6 BsubPc layers. Green-selective photodetectors with cutting-edge performance are thus realized, achieving a 25% increase in external quantum efficiency compared to all prior solution-based NBA implementations, as well as a nearly five-fold enhancement of the green-to-blue spectral rejection ratio. The merit of this approach is further illustrated by comparison with the corresponding fullerene-based photodetectors. By demonstrating an approach to solution-based NBA photodetectors with cutting-edge photoconversion efficiency and spectral selectivity, this study represents an important step toward printable, high-performance organic color sensors and imagers.